Working “With” Not “On” Disabled People: The Role of Hate Crime Research within the Community - Burch, Leah (Journal of interpersonal violence, 2024)
For many disabled people, violence can become an unwanted, yet ordinary part of everyday life. Often, these crimes are attributed to understandings of disabled people as vulnerable and largely, passive victims. Attending to the aims of this special issue, this paper aims to dismantle these stereotypes and attend to the unique ways that disabled people can resist and respond to hate crime through creative and collaborative research practices. Building upon this, I argue that there is a pressing need for hate studies researchers to work “with” and not “on” those who have experienced targeted violence. Working in this way builds upon long-standing efforts of disabled activists and disabilities studies researchers to challenge reductive research practices by working in more collective and inclusive ways. To demonstrate this, I reflect upon a project working in partnership with disabled people to create a disability hate crime toolkit. The toolkit, now published, shares accessible and informative resources that can be used to raise awareness about disability hate crime. While the focus of this paper is disability, I consider methods of collaboration, co-production and participation that can be drawn upon by researchers to respond to hate crime and interpersonal violence more broadly.